Gênero e ciência na ficção científica de Berilo Neves - Aline de Castro Lemos (2014)
This research proposes to analyze the dialogue between Berilo Neves considered to be the first author to systematically dedicate himself to science fiction in Brazil literature and the debates about countrys modernization and, in particular, about womens issue at 1920 and 1930 decades at Rio de Janeiro. While Neves speculations about scientific themes expressed certain understanding on the possibilities and consequences of his times scientific practices, they satirized his contemporary society, the feminine behavior being his favorite target. By means of a science fiction specific language, the author mobilized and elaborated representations about science and women, particularly about the places of one and another in a social change process. The research proposes, thus, to confront the following problem: in which way Neves writings articulate the ambiguities, tensions and contradictoriness of an experience of the changes going on in that society, especially in gender relations? The consulted sources cover primarily Neves science fiction tales, but comprehend also other text by him and contemporary journal material which account on his repercussion and related debates. Its analysis allowed the understanding that his writings have an ambiguous effect that combines wonder and suspicion towards scientific endeavors, but share with his time scientific language and assumptions which define gender roles and identities, as well as the desire for a traditional values preserving modernization. The plural and contradictory aspects of his writings regard to the sensibility of an experience of profound social and technological changes. That sensibility was also one of the reasons of the enormous repercussion of his work and the multiple opinions and understandings around it by his contemporary.